Understanding the structural and chemical changes of plant biomass following steam explosion pretreatment. Issue 1 (December 2017) - Auxenfans, Thomas; Crônier, David; Chabbert, Brigitte; Paës, Gabriel
Abstract Background Biorefining of lignocellulosic biomass has become one of the most valuable alternatives for the production of multi-products such as biofuels. Pretreatment is a prerequisite to increase the enzymatic conversion of the recalcitrant lignocellulose. However, there is still considerable debate regarding the key features of biomass impacting the cellulase accessibility. In this study, we evaluate the structural and chemical features of three different representative biomasses (Miscanthus ×giganteus, poplar and wheat straw), before and after steam explosion pretreatment at increasing severities, by monitoring chemical analysis, SEM, FTIR and 2D NMR. Results Regardless the biomass type, combined steam explosion pretreatment with dilute sulfuric acid impregnation resulted in significant improvement of the cellulose conversion. Chemical analyses revealed that the pretreatment selectively degraded the hemicellulosic fraction and associated cross-linking ferulic acids. As a result, the pretreated residues contained mostly cellulosic glucose and lignin. In addition, the pretreatment directly affected the cellulose crystallinity but these variations were dependent upon the biomass type. Important chemical modifications also occurred in lignin since the β-O -4′ aryl-ether linkages were found to be homolytically cleaved, followed by some recoupling/recondensation to β-β′ and β-5′ linkages, regardless the biomass type. Finally, 2D NMR analysis of the whole biomass showed that the pretreatment preferentially degraded the syringyl-type lignin fractions in miscanthus and wheat straw while it was not affected in the pretreated poplar samples. Conclusions Our findings provide an enhanced understanding of parameters impacting biomass recalcitrance, which can be easily generalized to both woody and non-woody biomass species. Results indeed suggest that the hemicellulose removal accompanied by the significant reduction in the cross-linking phenolic acids and the redistribution of lignin are strongly correlated with the enzymatic saccharification, by loosening the cell wall structure thus allowing easier cellulase accessibility. By contrast, we have shown that the changes in the syringyl/guaiacyl ratio and the cellulose crystallinity do not seem to be relevant factors in assessing the enzymatic digestibility. Some biomass type-dependent and easily measurable FTIR factors are highly correlated to saccharification.